Histopathological changes resulting from selective internal radiotherapy (SIRT). Issue 5 (15th February 2018) - Justinger, Christoph; Gruden, Juliana; Kouladouros, Konstantinos; Stravodimos, Christos; Reimer, Peter; Tannapfel, Andrea; Binnenhei, Martin; Bentz, Martin; Tatsch, Klaus; Rüdiger, Thomas; Schön, Michael R.
Abstract : Background: Selective internal radiotherapy (SIRT) has emerged as an effective therapy for patients with liver malignancies. Here, we report our analysis of histopathological changes in tumors and healthy liver tissue after SIRT and liver resection. Our main intent was to determine if specific histopathological changes occur in tumor and normal liver tissues. Methods: We identified 17 patients in whom SIRT was applied to achieve liver resectability. Samples were taken from the resected liver tissue. The tumor, tumor peripheries, and tumor‐free tissue were examined microscopically. Results: Microspheres were identified in the vascular tumor bed, tumor‐free liver, and portal tract. More microspheres were detected in the tumor than in the healthy liver tissue. When the effects of SIRT were analyzed, most patients showed a partial pathological response. Specific histopathological changes could not be described. We did not find any typical signs of radiation‐induced hepatitis in healthy liver tissue. Conclusions: Our findings support the clinical experience of effective tumor control after SIRT together with minimal impairment of healthy liver tissue. The observed histopathological changes suggest that SIRT might play a role in preoperative downsizing of liver malignancies.